Are Health Agencies Designated as Research Centers in Nepal Conducting Adequate Researches ? - Sah, Arun Kumar; Belbase, Pradeep; Pandey, Ashok; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2019)
Background: In Nepal, promoting quality research and enhancing research capacity is being accomplished through Nepal Health Research Council (NHRC). It also plays an authorized body to regulate, monitor and coordinate health research centers by maintaining the highest level of ethical standards. The aim of this study is to explore situation of health agencies designated as research center in Nepal. Methods: A cross sectional descriptive study design was used to carry out monitoring and follow up of activities of research centre of all seven provinces of Nepal that had title “Research” in their title name from January 2018 to July 2018. Results: There were only 81 research centers in Nepal and more than half (55 percent) of these have been found in Kathmandu valley, Province 3. Research found that 82.3% so called research centers were just health service provider and 10% of research institute were research based and just 5% have the core objectives of research. Likewise, 30% of research institute were actually involved in health related researches whereas large proportion (70%) of research institute were not involved in any kind of research work. Surprisingly, only 37.5% have taken ethical approval to conduct the designated research. Conclusions: Only one tenth of the research centers have mentioned research as their core business. However, less than one third of such centers were involved in heath research, and out of which, only 28 percent took ethical permission. Most of the research organizations want to conduct research but they do not have required research skills and competent manpower to carry out research. Keywords: Health research centers; monitoring; Nepal.